Preparation of TiO2-SiO2 using Rice Husk Ash as Silica Source and The Kinetics Study as Photocatalyst in Methyl Violet Decolorization - Is Fatimah; Ahmad Said; Uun Ayil Hasanah (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
Preparation, characterization and utilization of TiO2-SiO2 as photocatalyst for methyl violet (MV) decolorization has been conducted. In this research, preparation of TiO2-SiO2 was developed based on natural renewable silica source; rice husk ash (RHA) via a sol-gel technique. The composite was formed by the dispersing of titanium isopropoxide as titania precursor into the gel of silica followed by aging, drying and calcination. The TiO2-SiO2 sample was characterized by powder X-ray diffraction (XRD), diffuse reflectance-UV Visible spectrophotometric analysis (DRUV-Vis), gas sorption analyzer and Scanning electron micrograph (SEM) before its utilization as photocatalyst in methyl violet photooxidation. As comparison to the physicochemical character study, the synthesis of TiO2-SiO2 by using tetraethyl ortosilicate (TEOS) was performed as a confirmation. Result showed that prepared TiO2-SiO2 has the character similar to TiO2-SiO2 as synthesized by TEOS precursor. The formation of crystalline titania in anatase and rutile phase was identified with increasing surface porosity data and the value of band gap energy which sufficiently contribute to a photocatalytic mechanism. The character data are in line with the kinetic data of methyl violet decolorization. From the compared photooxidation, photolysis, photocatalysis and adsorption process, it can be concluded that TiO2-SiO2 acts efficiently as a photocatalyst. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)